Gender difference in handgrip strength of Italian children aged 9 to 10 years - Montalcini, Tiziana (Ital J Pediatr, 2016)
BACKGROUND: Handgrip strength is an index of nutritional status which correlates to morbidity and mortality in young. It differs in adults and adolescents between gender. However, it is no clear whether a difference exists also in children aged 9 to 10 years, and which are the factors influencing it. Furthermore, data of Handgrip strength of Italian schoolchildren are lacking. Aim of this study was to provide Handgrip strength value from a sample of healthy Italian schoolchildren aged 9 to 10 years and to determine which factors affect grip strength at this age. METHODS: We enrolled 137 children (boys n =66; girls n = 71) who underwent a body mass index and Handgrip strength measurement. Handgrip strength was assessed by an hydraulic hand dynamometer. RESULTS: The mean handgrip strength value was 13.8 ± 4.0 for girls and 15.2 ± 3.0 kg for boys (p = 0.04) thus, we found a significant difference between gender. We have not found a significant differences in anthropometric parameters between gender. In the univariate analysis Handgrip strength was associated with age, BMI, height, weight and gender (p < 0.001 for age, p < 0.001 for BMI, p < 0.001 for height, p < 0.001 for weight and p < 0.04 for gender). The Multivariate linear regression analysis showed that age, BMI and gender were all correlated to grip force. CONCLUSION: We found a significant difference in grip strength between healthy Italian schoolchildren aged 9 to 10 years. This parameter seems to be primarily influenced by gender. Our investigation is important since currently data regarding the reference values of HGS for Italian children are lacking.